EFFECT OF SHWETHA PARPATI IN UNCOMPLICATED LOWER URINARY TRACT E.COLI INFECTION - A CASE REPORT - Ratna Prava Misra; Krishnakumar K (International Journal of Ayurveda and Pharma Research, 2021)
UTI is one of the most common infections which is faced by women in this era. Even though the pathogens like bacteria, virus, fungi, protozoans etc are causing the infection, E.coli is the predominant bacteria causing UTI. If it is not treated in time it can cause organ damage. The symptoms of UTI are similar to the disease Mutrakrichra in Ayurveda. Even Though Antibiotics are helpful, the resistance of bacteria can increase and the options for treatment can decrease. It is observed that study of Swetha parpati gives good outcomes while treating the UTI caused by E-coli which is used by the Ayurveda community. A 42 year old female patient who was diagnosed as having Lower urinary tract infection caused by E-coli for the last 5 months. She was administered with the drug Shwetaparpati for 14 days, by using subjective and objective assessment criteria showed the significant outcome. ICD 10 CM-N39.0 is used for selection & assessment. Fever, Chillness, urgency, Dysuria, Lower abdominal pain with bacteriuria (E.Coli), and pyuria were the signs and symptoms. After the treatment symptoms vanished and on the follow up concluded that there was no presence of E. Coli bacteria.